Social practice theory and mathematics teacher education: a conversation between theory and practice - Adler, Jill (NOMAD Nordic Studies in Mathematics Education, 2000)
This is an expanded version of a paper and presentation at a conference on Social Constructivism, Social Practice Theory and Socio-cultural Theory: Relevance and Rationalisation in Mathematics Education in Norway, March 2000.